Seismic Analysis of Reinforced Concrete Buildings in South of Iraq based on Different Codes - A. B. Al-Jassim, Samir; Abdul Kareem Raheem, Haider (International Journal of Engineering and Technology, 2018)
Buildings in south of Iraq were designed for gravity loads only. Recent studies showed that the Badra-Amarah fault at the Iraq-Iran boarder is an active fault and could suffer a major damage. Hence seismic evaluation of existing buildings is getting more importance. The objective of this paper is to assess the seismic performance of two reinforced concrete buildings with six floors each, one has a shear wall and the other has not. The concentrated plasticity with nonlinear time history is adopted for the analysis. The spectrum matching method is used to scale three time-acceleration records to the expected seismic level in the region. Three different codes are used for the analysis, the International building code-2012, the Uniform building code-1997 and the Iraqi seismic code-2017. Comparison of results showed that IBC-2012 gave the most conservative results in displacements, number and performance of plastic hinges and base shear. The Iraqi code gave the least values within 60% for the base shear and 18-50% for drifts. As a conclusion, the analyzed buildings are a little beyond the elastic level according to the Iraqi code, beyond the immediate occupancy level according to the UBC-1997 and near the collapse prevention level according to IBC-2012.